Bromodomain and BET family proteins as epigenetic targets in cancer therapy: their degradation, present drugs, and possible PROTACs. Issue 2 (24th December 2020) - Muddassir, Mohd.; Soni, Kunjal; Sangani, Chetan B.; Alarifi, Abdullah; Afzal, Mohd.; Abduh, Naaser A. Y.; Duan, Yongtao; Bhadja, Poonam
Abstract : Alteration in the pattern of epigenetic marking leads to cancer, neurological disorders, inflammatory problems etc. Abstract : Alteration in the pattern of epigenetic marking leads to cancer, neurological disorders, inflammatory problems etc. These changes are due to aberration in histone modification enzymes that function as readers, writers and erasers. Bromodomains (BDs) and BET proteins that recognize acetylation of chromatin regulate gene expression. To block the function of any of these BrDs and/or BET protein can be a controlling agent in disorders such as cancer. BrDs and BET proteins are now emerging as targets for new therapeutic development. Traditional drugs like enzyme inhibitors and protein–protein inhibitors have many limitations. Recently Proteolysis-Targeting Chimeras (PROTACs) have become an advanced tool in therapeutic intervention as they remove disease causing proteins. This review provides an overview of the development and mechanisms of PROTACs for BRD and BET protein regulation in cancer and advanced possibilities of genetic technologies in therapeutics.